Smart Sponge for Fast Liquid Absorption and Thermal Responsive Self‐Squeezing - Cui, Ying; Wang, Yujie; Shao, Ziyu; Mao, Anran; Gao, Weiwei; Bai, Hao (Advanced materials (Weinheim), 2020)
Liquid absorption and recycling play a crucial role in many industrial and environmental applications, such as oil spill cleanup and recovery, hemostasis, astronauts' urine recycling, and so on. Although many liquid absorbing materials have been developed, it still remains a grand challenge to achieve both fast absorption and efficient recycling in a cost‐effective and energy‐saving manner, especially for viscous liquids such as crude oil. A smart polyurethane‐based porous sponge with aligned channel structure is prepared by directional freezing. Compared to common sponges with random porous structure, the as‐prepared smart sponge has larger liquid absorption speed due to its lower tortuosity and stronger capillary (“tortuosity effect”). More importantly, the absorbed liquid can be remotely squeezed out due to a thermally responsive shape memory effect when the sponge is heated up. Such smart sponges with well‐defined porous structure and thermal responsive self‐squeezing capability have great potential in efficient liquid absorption and recycling. A smart porous sponge with aligned channel structure is fabricated by directional freezing. Compared to sponges with random porous structure, the as‐prepared sponge has larger liquid absorption speed due to its lower tortuosity. The absorbed liquid can be remotely squeezed out due to thermally responsive shape memory effect. Such sponges have great potential in efficient liquid absorption and recycling.